Constitutionality control in Latin America - Fonseca Sarmiento, Carlos Alberto (2022)
In this article, the author describes the different constitutionality control systems incorporated in Latin American countries to identify the best options to optimize the defense of the Constitution. For this purpose, the author identifies the 6 most used criteria to classify these systems. Finally, using these criteria, the author makes an evaluation of constitutionality control in Peru.